Gladys Black letter to Nicholas S. Halmi regarding bird sightings, March 6, 1978 - Black, Gladyset al (1978)
Letter from Gladys Black to Nicholas S. Halmi regarding bird sightings, March 6, 1978. The document contains numerous handwritten annotations throughout. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter, 1977-1978. Epson - sheet feed/flatbed